The German translation of the Oxford utilitarianism scale: Validation and the impact of the Covid-19 pandemic on the observations - Aistė Ambrasė; Malte Hendrickx; Melina Grahlow; Hong Yu Wong; Birgit Derntl (PLoS ONE, 2025)
The study of utilitarian inclinations is probably the most experimentally investigated aspect of morality. The Oxford Utilitarianism Scale has been developed to provide a self-report tool for reliable measurement of utilitarian views while addressing serious methodological issues with previous measures. In this study, we have translated and validated a German version of the Oxford Utilitarianism Scale (OUS-DE). The scale consists of two subscales: Impartial Beneficence (IB-DE) and Instrumental Harm (IH-DE). We conducted a procedure in a general German sample (N S1 = 378, 243 women, M age = 25.37) before the Covid-19 pandemic. A confirmatory factor analysis demonstrated a good fit of a two-factor model for OUS-DE, while internal consistency and construct reliability were acceptable. Both in the pre-pandemic and the post-pandemic sample (N S2 = 348, 206 women, M age = 24.61) we found a sex/gender difference, with women scoring significantly higher in the IB-DE subscale than men. We also found that the mean agreement with the IB-DE subscale decreased after the pandemic. In a separate third sample (N S3 = 39, 19 women, M age = 23.72), we observed an inverse U-shape relationship between moral behavior related to quarantine requirements and the IH-DE subscale, as measured during the peak pandemic restrictions in late 2020. Repeated OUS-DE measurement in this sample showed stability in responders’ utilitarian beliefs post-pandemic. In sum, OUS-DE is the first available measurement of utilitarian inclinations in German. The scale will enable further research on how utilitarian preconceptions affect behavior in German-speaking populations.